2004
DOI: 10.1002/cncr.20505
|View full text |Cite
|
Sign up to set email alerts
|

A perspective from countries using organized screening programs

Abstract: Cancer screening may be offered to a population opportunistically, as part of an organized program, or as some combination of the preceding two options. Organized screening is distinguished from opportunistic screening primarily on the basis of how invitations to screening are extended. In organized screening, invitations are issued from centralized population registers. In opportunistic screening, however, due to the lack of central registers, invitations to screening depend on the individual's decision or on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
129
1
10

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 190 publications
(149 citation statements)
references
References 59 publications
(53 reference statements)
2
129
1
10
Order By: Relevance
“…[15] The mean age in the present study was 37.5 years which was comparable to the study of Chang et al [16] in which the mean age was 37 years. The mean age was slightly higher in other studies.…”
Section: Discussionsupporting
confidence: 88%
“…[15] The mean age in the present study was 37.5 years which was comparable to the study of Chang et al [16] in which the mean age was 37 years. The mean age was slightly higher in other studies.…”
Section: Discussionsupporting
confidence: 88%
“…Compared to the alternative of opportunistic screening, 9 organized screening puts a much greater emphasis on the quality of the screening process as measured by factors such as, tumour characteristics, cancer detection rates and false-positive biopsy rates (Miles et al, 2004). Thus, it provides better protection against the harms of screening-including overscreening, poor quality, and complications of screening-and poor follow-up of those who test positively (Levin et al, 2012, Miles et al, 2004.)…”
Section: Institutional Factorsmentioning
confidence: 99%
“…Thus, it provides better protection against the harms of screening-including overscreening, poor quality, and complications of screening-and poor follow-up of those who test positively (Levin et al, 2012, Miles et al, 2004.) Accordingly, Strumpf, Chai and Kadiyala (2010) found that the implementation of an organized mammography screening program in Quebec strongly increased adherence to cancer screening guidelines and screening uptake.…”
Section: Institutional Factorsmentioning
confidence: 99%
“…Este recomenda que rastreamento do câncer de mama por mamografia seja realizado em mulheres entre 50 e 69 anos, com no máxi-mo dois anos de intervalo 9,10 . Entretanto, o rastreamento é de forma oportunística 11 , no qual a solicitação do exame dependerá do interesse da mulher em procurar o serviço de saúde 12,13 . Além disto, não há evidência de que o programa de controle do câncer de mama seja efetivo 11 , pois não ocorre acompanhamento dos casos suspeitos, premissas nos rastreamentos organizados 12,13 .…”
Section: Introductionunclassified